2014
DOI: 10.1016/s1473-3099(14)70828-x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging novel and antimicrobial-resistant respiratory tract infections: new drug development and therapeutic options

Abstract: The emergence and spread of antimicrobial-resistant bacterial, viral, and fungal pathogens for which diminishing treatment options are available is of major global concern. New viral respiratory tract infections with epidemic potential, such as severe acute respiratory syndrome, swine-origin influenza A H1N1, and Middle East respiratory syndrome coronavirus infection, require development of new antiviral agents. The substantial rise in the global numbers of patients with respiratory tract infections caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 145 publications
0
70
0
4
Order By: Relevance
“…Useful antiviral agents for (MERS-CoV) infection include neutralizing antibody, convalescent plasma, polyclonal human immunoglobulin, Equine F(ab')2 antibody fragments, anti-S monoclonal antibodies and interferons [74]. Other medications could be repurposed for use against MERS-CoV, including ribavirin, protease inhibitors (lopinavir, nelfinavir), cyclophilin inhibitors (cyclosporine, alisporivir), chloroquine, mycophenolic acid, nitazoxanide, recombinant human mannose-binding lectin and siRNA to key MERS-CoV genes [74]. Approved antiviral agents can be repurposed for use against emerging viral infections to shorten the time from virus discovery to treatment availability [75].…”
Section: Currently Available Antiviral Agents and Vaccinesmentioning
confidence: 99%
“…Useful antiviral agents for (MERS-CoV) infection include neutralizing antibody, convalescent plasma, polyclonal human immunoglobulin, Equine F(ab')2 antibody fragments, anti-S monoclonal antibodies and interferons [74]. Other medications could be repurposed for use against MERS-CoV, including ribavirin, protease inhibitors (lopinavir, nelfinavir), cyclophilin inhibitors (cyclosporine, alisporivir), chloroquine, mycophenolic acid, nitazoxanide, recombinant human mannose-binding lectin and siRNA to key MERS-CoV genes [74]. Approved antiviral agents can be repurposed for use against emerging viral infections to shorten the time from virus discovery to treatment availability [75].…”
Section: Currently Available Antiviral Agents and Vaccinesmentioning
confidence: 99%
“…A recent randomized controlled trial in Russia showed that this drug can hasten the resolution of symptoms (Kiselev et al, 2015). Other novel antivirals, such as DAS181, are still undergoing clinical trials (Zumla et al, 2014). Convalescent blood products, which have both antiviral and immunomodulatory activity, have improved the survival of patients in the 1918 and 2009 A(H1N1) pandemics (Hung et al, , 2013Luke et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…T-705 was approved in Japan for restricted use against NAI-resistant pandemic influenza viruses (15) and is currently in phase 3 trials in Europe and the United States (https://clinicaltrials.gov/ct2/results ?termϭT-705&SearchϭSearch). According to available clinical information, its antiviral effects are similar to those of oseltamivir (16), giving a statistically significant decrease in symptom duration (17). An important structural element in T-705 is the carboxamide moiety, which is also present in the broad RNA virus inhibitor ribavirin.…”
mentioning
confidence: 98%